1983
DOI: 10.2307/1191559
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and Technological Innovation in the Chemical Industry

Abstract: The observation that innovation often occurs without R&D has important implications for the argument that, because regulation may divert resources from R&D, innovation is necessarily adversely affected. See infa section III(D) () (e). 4. S. MYERS & D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 0 publications
1
45
0
Order By: Relevance
“…This perspective has greatly influenced the literature on environmental management and prompted calls for more stringent government regulation to reduce the use of EOP treatment (Ashford andHeaton 1983, Porter andvan der Linde 1995). Yet, despite this prediction's importance to both research and practice, it has not been well tested empirically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This perspective has greatly influenced the literature on environmental management and prompted calls for more stringent government regulation to reduce the use of EOP treatment (Ashford andHeaton 1983, Porter andvan der Linde 1995). Yet, despite this prediction's importance to both research and practice, it has not been well tested empirically.…”
Section: Discussionmentioning
confidence: 99%
“…Scholars have arrived at an explanation by drawing on organizational theory that predicts managers will tend to pick the least disruptive response to new requirements (Galbraith 1974, Thompson 1967. According to this logic, EOP treatment is an attractive solution for managers, because although such systems can be financially costly to install and operate, they do not usually require disturbance of existing operations (Ashford andHeaton 1983, Cebon 1992). Indeed, to prevent firms from taking this easy way out, some scholars have suggested that government regulation should be stringent enough to discourage the use of EOP systems (Kemp 2000).…”
Section: Eop Treatment and Detrimental Impacts Onmentioning
confidence: 99%
“…Similarly, the analysis of Grabowski, Vernon and Thomas (1978), reformulating a model previously developed by Baily (1972), suggests that other non-regulatory factors have an important aggregative effect on innovation. Thus, the decline in US productivity was not only caused by the tighter regulation introduced with the 1962 Amendments, but also by other factors such as the rise in costs, as a result of advances in the technology of safety testing, a general depletion of research opportunities and the Thalidomide incident which has made firms and physician more cautious (see also Ashford and Heaton, 1983;Backhaus, 1983;Wardell and Sheck, 1984;Wiggins, 1984).…”
Section: Some More Empirical Studies On Product Safety Regulationmentioning
confidence: 99%
“…work health and hazards and energy may provide the basis for competitive advahtages (e.g. Ashford & Heaton 1983). The survey revealed that 24.2 percent of all firms had experienced positive consequences of public regulation.…”
Section: Contacts To Bureaucratsmentioning
confidence: 99%